Application of Bacillus velezensis NJAU-Z9 Enhanced Plant Growth Associated with Efficient Rhizospheric Colonization Monitored by qPCR with Primers Designed from the Whole Genome Sequence - Yang Zhang; Xu Gao; Shuai Wang; Chengzhi Zhu; Rong Li; Qirong Shen (Current Microbiology, 2018)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Plant-mediated competition facilitates a phoretic association between a gall mite and a psyllid vector - Jianling Li; Sai Liu; Kun Guo; Fan Zhang; Haili Qiao; Jianmin Chen; Mengke Yang; Xiu Zhu; Rong Xu; Changqing Xu; Jun Chen (Experimental and Applied Acarology, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Synthesis, antitumor evaluation and molecular docking study of a novel podophyllotoxin-lonidamine hybrid - Lei Zhang; Jie Zheng; Ying Rong; Chengli Yang; Li Long; Yingshu Xu; Yongzheng Chen; Jing Wang; Qizheng Yao (Medicinal Chemistry Research, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Elatostema brachyodontum subsp. lengshuiheensis (Urticaceae), a new subspecies from Guizhou, China - Yun Lin; Ming-Tai An; Zhi-Rong Yang; Yan-Qiang Dai; Deng-Li Yu (Kew Bulletin, 2018)

Genetic variability of wildlife-derived Sarcoptes scabiei determined by the ribosomal ITS-2 and mitochondrial 16S genes - Chun-Yan Li; Yin Sun; Yue Xie; Xuan Zhou; Xiao-Bin Gu; Wei-Ming Lai; Xue-Rong Peng; Guangyou Yang (Experimental and Applied Acarology, 2018)

Srk1 kinase, a SR protein‐specific kinase, is important for sexual reproduction, plant infection and pre‐mRNA processing in Fusarium graminearum - Guanghui Wang; Peng Sun; Ziwen Gong; Lianfeng Gu; Yi Lou; Wenqin Fang; Lianhu Zhang; Li Su; Tao Yang; Baohua Wang; Jie Zhou; Jin‐Rong Xu; et al. (Environmental Microbiology, 2018)
Summary SR protein‐specific kinases (SRPKs) uniquely with a spacer region are important splicing factors from yeast to human. However, little is known about their biological functions in filamentous fungi. Therefore, we characterized a SRPK called SRK1 in wheat scab fungus Fusarium graminearum . Our data showed that Srk1 is required for vegetative growth, sexual reproduction and plant infection, and plays critical roles in pre‐mRNA alternative splicing and gene expression. Remarkably, we found that Srk1 displayed dynamic shuttling between cytoplasm and the nucleus, which is regulated by the divergent spacer domain rather than its kinase activity, suggesting a regulatory mechanism for Srk1. Interestingly, Srk1‐GFP also localized to the septal pores, indicating a possible role of Srk1 unrelated to mRNA processing. Although both K1 and K2 lobes of the kinase domain are essential for Srk1 functions, the K2 but not K1 lobe is responsible for the septal pore localization. Lastly, we established that Srk1 physically interacts with the two SR proteins, FgNpl3 and FgSrp1. Overall, our results indicated that SRK1 regulates fungal development, plant infection and mRNA processing by phosphorylation of other splicing factors including SR proteins, and the spacer domain regulates the functions of Srk1 by modulating its nucleocytoplasmic shuttling.

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Damage to buildings and structures due to recent devastating wind hazards in East Asia - Qingshan Yang; Rong Gao; Fan Bai; Tian Li; Yukio Tamura (Natural Hazards, 2018)

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L. - Lifei Luo; Rong Huang; Aidi Zhang; Cheng Yang; Liangming Chen; Denghui Zhu; Yongming Li; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Functional & Integrative Genomics, 2018)

Avalanche activity and characteristics of its triggering factors in the western Tianshan Mountains, China - Jian-sheng Hao; Fa-rong Huang; Yang Liu; Chukwudi Amanambu Amobichukwu; Lan-hai Li (Journal of Mountain Science, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Agrobacterium tumefaciens-mediated transformation system for the important medicinal plant Dendrobium catenatum Lindl - Ji Chen; Li Wang; Jianbin Chen; Jin Huang; Fan Liu; Rong Guo; Li Yang; Aby Grabon; Ke Zhao; Fanlei Kong; Chen Liu; Mengliang Tian (In Vitro Cellular & Developmental Biology - Plant, 2018)

Pleiotropic effects of the wheat domestication gene Q on yield and grain morphology - Quan Xie; Na Li; Yang Yang; Yulong Lv; Hongni Yao; Rong Wei; Debbie L. Sparkes; Zhengqiang Ma (Planta, 2018)

Effects of enhanced ultraviolet-B radiation, water deficit, and their combination on UV-absorbing compounds and osmotic adjustment substances in two different moss species - Rong Hui; Ruiming Zhao; Guang Song; Yixuan Li; Yang Zhao; Yanli Wang (Environmental Science and Pollution Research, 2018)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

Anti-oral common pathogenic bacterial active acetylenic acids from Thesium chinense Turcz - Chang Liu; Xiao-Tian Li; Rong-Rong Cheng; Zhu-Zhen Han; Li Yang; Zhong-Chen Song; Zheng-Tao Wang (Journal of Natural Medicines, 2018)

Agricultural non-point source pollution management in a reservoir watershed based on ecological network analysis of soil nitrogen cycling - Wen Xu; Yanpeng Cai; Qiangqiang Rong; Zhifeng Yang; Chunhui Li; Xuan Wang (Environmental Science and Pollution Research, 2018)

Maternal doubled haploid production in interploidy hybridization between Brassica napus and Brassica allooctaploids - Shaohong Fu; Liqin Yin; Mingchao Xu; Yun Li; Maolin Wang; Jin Yang; Tingdong Fu; Jisheng Wang; Jinxiong Shen; Asif Ali; Qiong Zou; Bin Yi; et al. (Planta, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)